The Role of Gratitude and Family Support on Psychological Well-Being of Mothers with Autistic Children - Hizbullah, Kahfi; Mulyati, Rina (Universitas Muhammadiyah Yogyakarta, 2022)
Having a child with an autistic spectrum disorder is a challenge for parents, especially mothers, which can hinder the fulfillment of optimal psychological functions so that the mother’s psychological well-being is disturbed. Internal situations such as gratitude and the presence of external support from the family can be factors that can encourage increased psychological well-being in mothers. This study observed the effects of gratitude and family support on mothers’ psychological well-being with children with an autism spectrum disorder. The instruments in this study used the gratitude scale, the family support scale and Ryff’s Psychological Well-Being Scales-short version distributed online. The subject in this study was 98 people, and the data collected were analyzed using the Doubled Linear Regression test using JASP software. The results showed the significance value of p<0.05; thus, gratitude and family support had a role or effect on mothers’ psychological well-being with children with an autism spectrum disorder. Meanwhile, the effective contribution for gratitude was 17.39%, and family support was 21.53%. For future research, gratitude and emotion-based therapies such as emotion regulation training can be used as an intervention in experimental research to improve psychological well-being.